PENGARUH BUDAYA ORGANISASI DAN KEDISIPLINAN TERHADAP KINERJA DOSEN DI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Indah Respati Kusumasari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2017)
This study aims to determine the influence of organizational culture and discipline on the performance of Lecturer Abdurachman Saleh Situbondo University. This research is quantitative research, there are 2 independent variable that is Organization Culture (X1) and Discipline (X2) and dependent variable that is Lecturer Performance (Y). Indicator used Organizational culture variable (X1) that is innovation and risk taking, attention to detail, outcome orientation, people orientation, aggressiveness and stability. Indicators of discipline variables (X2) are attendance, obedience to work regulations, adherence to work standards, high level of vigilance and ethical work. Indicators of employee performance variables are quality, quantity, timeliness, cost effectiveness and personal relationships. The way of data collection is by way of observation, questionnaires and documentation. The data analysis used is multiple linear regression. The result of this research is organizational culture have a significant effect to the performance of lecturer of Abdurachman Saleh Situbondo University. Discipline has a significant effect on the performance of university lecturer Abdurachman Saleh Situbondo. Organizational culture and discipline have a significant effect on the performance of the lecturers of Abdurachman Saleh Situbondo University